Self‐reported involvement in road traffic crashes in Kenya: A cross‐sectional survey of a nationally representative sample. Issue 5 (14th September 2022) - Shaikh, Masood Ali; Lule, Herman; Bärnighausen, Till; Lowery Wilson, Michael; Abio, Anne
Abstract: Background: Road traffic crashes (RTCs) are a global public health burden whose resulting morbidity and mortality disproportionately impact low‐ and middle‐income countries with stressed health systems. There is a paucity of published studies that evaluate the sociodemographic distribution of RTCs using nationally representative samples from the African region. Aim: To examine population‐wide associations between sociodemographic factors and involvement in RTCs in Kenya. Methods: Data were obtained from the 2014 Kenyan Demographic Health Survey, representing all 47 counties in Kenya, from May to October of 2014. We estimated the prevalence of RTCs and utilized logistic regression for bivariate and multivariable analyses to determine the sociodemographic factors associated with RTCs. Study variables included age, place of residence, household wealth index, educational attainment, and history of alcohol consumption. We computed odds ratios (ORs) and their corresponding 95% confidence intervals (CIs). Results: A higher prevalence was reported among men (8.76%) versus women (3.22%). The risk factors among men included being 20−34 years of age, living in a rural area (OR 1.38, 95% CI 1.09, 1.74), drinking alcohol (OR 1.33, 95% CI 1.11, 1.59), and having not higher than a primary (OR 1.90, 95% CI 1.19, 3.03) or secondary (OR 1.68, 95% CI 1.04, 2.71) education. The strongest risk factors for women included the being aged 45−49 (OR 2.30, 95% CI 1.44, 3.67) and 20−24 years (OR 1.81, 95% 1.17, 2.79) as well as being in the fourth wealth quintile (OR 1.83, 95% CI 1.15, 2.91). Conclusion: Men and the most economically productive age groups were more likely to report being involved in RTCs. Strategies to reduce the occurrences of RTCs should prioritize the most vulnerable sociodemographic groups.